Penerapan Media Interaktif dalam Meningkatkan Hasil Belajar Pendidikan Agama Buddha Siswa Kelas III SD Maitreyawira Dumai - Dewi Triyani; Irawati Irawati; Hosan Hosan (STAB Maitreyawira, 2023)
The purpose of this action research is to determine the implementation of learning and the application of interactive media in improving the learning outcomes of Buddhist education for third grade students of SD Maitreyawira Dumai. The results ofthe research with the procedures for planning, implementing, observing, and reflecting. It has been implemented well, as indicated by the increase in learning outcomes, the average score of students shows an increase in learning outcomes from 44 in the pre-cycle increasing to 73 in the first cycle, increasing to 87 in the second cycle until all students complete (≥73 KKM) in the first cycle. received Buddhist Education lessons with the application of interactive learning media, in the percentage there was an increase in learning outcomes by 52% in the first cycle and 48% in the second cycle to 100%. This shows that the application of interactive learning media is successfully understood by students, Buddhist teachers are more involved in student activity inthe learning process by applying interactive learning media based on interactive PPT which is fun and interesting.